(untitled) (Bangladesh Journal of Neuroscience, 2019)
Background: Internal carotid artery (ICA) is one of the commonest site stenosis in patients with ischemic stroke. There is difference in the distribution of stenosis among different sites of cerebral infarct.Volume and severity of cerebral infarct may also depend on the degree of stenosis. To plan efficient evaluation and treatment of individual patient of ischemic stroke, the responsible clinician must be familiar with the relative probability of finding occlusive lesions at various sites within the vascular tree. Objective: The objective of this study was to evaluate the angiographic pattern of ICA stenosis among different types of cerebral infarct. Materials and Methods: We evaluated 53 ischemic stroke patients from indoor, outdoor, stroke and neuro intervention clinic, BSMMU. CT scan and/ or MRI of brain were done to each patient to confirm the diagnosis. After vascular imaging, the degree of stenosis was measured by the NASCET formula. Results: Cervical segment of ICA was most commonly [n=45(84.9%)] encountered site of stenosis and total occlusion of ICA was always observed in cervical segment. Among patients with moderate stenosis (n=15) of ICA, 6(40.0%) presented with subcortical infarction, 4(26.7%) presented with lacunar infarction and 5(33.0%) presented with territorial infarction. In case of severe stenosis (n=23), territorial, lacunar and watershed infarct were 9(39.1%), 8(34.8%) and 2(8.7%) respectively. Whereas total occlusion (n=15) of ICA presented as either territorial infarction [n=11(73.3%)] or watershed infarction [n= 4(26.7%)]. These differences between severity of stenosis and subtype of infarct were also significant (p-value = 0.003).A total of 25 patients presented with territorial infarction, mostly MCA territory [n=23(92%)]. Conclusion: With increasing severity of stenosis, the infarct burden rises. ICA stenosis of e”70% mainly presented as territorial infarction whereas, watershed infarct was an indicator of severe stenosis. Bangladesh Journal of Neuroscience 2019; Vol. 35 (2): 69-77